Using plant spectral response curves in detecting plant stress - Orych, Agata; Walczykowski, Piotr; Dąbrowski, Rafał; Kutyna, Edyta (Ecological Questions, 2014)
Understanding the way in which electromagnetic radiation interacts with vegetation is extremely important when studying the possibility of using new remote sensing technologies for monitoring forests and crops. Remote sensing methods enable an early detection of changes occurring within plants, simplifying the locating of affected areas and determining the severity of the changes. The optical properties of leaves (reflection and absorption coefficients) in selected segments of leaves in different ranges of the electromagnetic spectrum may be useful in detecting any deficiencies or surplus of selected substances which are essential for plant growth and development. Changes in the spectral response curves of damaged leaves can be cause both by changes in the leaf structure (Chandrasekharan 2005; Jacquemoud & Ustin 2008) and biochemical changes within the plant (Chandrasekharan 2005). A series of experiments was conducted at the Military University of Technology in Warsaw using a terrestrial hyperspectral system. Spectral reflection coefficients acquired from imagery in the 420–1100 nm range have enabled the establishing of how various growing conditions affect vegetation and their spectral response curves.